Observation and properties of the orbitally excited Bs2* meson - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We report the direct observation of the excited L=1 state Bs2* in fully reconstructed decays to B+K-. The mass of the Bs2* meson is measured to be 5839.6±1.1(stat)±0.7(syst)MeV/c2, and its production rate relative to the B+ meson is measured to be [1.15±0.23(stat)±0. 13(syst)]%. © 2008 The American Physical Society.